Analisis Motivasi Kerja, Disiplin Kerja dan Insentif Terhadap Kinerja Karyawan - Ahmad Aswan Waruwu; Lamtiur Simanullang (Forum Kerjasama Pendidikan Tinggi, 2022)
The research analysis aims to determine whether work motivation, work discipline and incentives simultaneously have a positive and significant effect on employee performance at PT Mayora Indah Tbk West Medan. The data analysis technique used is the associative method with the help of the SPSS version 16.0 program. This study uses multiple linear regression analysis. The sample in this study were 68 respondents. Primary data collection using a questionnaire. The results showed that work motivation partially positive and significant effect on employee performance at PT Mayora Indah Tbk West Medan. Work discipline partially positive and significant effect on employee performance at PT Mayora Indah Tbk West Medan. Incentives partially positive and significant effect on employee performance at PT Mayora Indah Tbk West Medan. Work motivation, work discipline and incentives simultaneously